Hepatic hydrothorax: clinical review and update on consensus guidelines. Issue 4 (7th August 2016) - Al-Zoubi, Rana Khazar; Abu Ghanimeh, Mouhanna; Gohar, Ashraf; Salzman, Gary A.; Yousef, Osama
ABSTRACT: Hepatic Hydrothorax (HH) is defined as a pleural effusion greater than 500 ml in association with cirrhosis and portal hypertension. It is an uncommon complication of cirrhosis, most frequently seen in association with decompensated liver disease. The development of HH remains incompletely understood and involves a complex pathophysiological process with the most acceptable explanation being the passage of the ascetic fluid through small diaphragmatic defects. Given the limited capacity of the pleural space, even the modest pleural effusion can result in significant respiratory symptoms. The diagnosis of HH should be suspected in any patient with established cirrhosis and portal hypertension presenting with unilateral pleural effusion especially on the right side. Diagnostic thoracentesis should be performed in all patients with suspected HH to confirm the diagnosis and rule out infection and alternative diagnoses. Spontaneous bacterial empyema and spontaneous bacterial pleuritis can complicate HH and increase morbidity and mortality. HH can be difficult to treat and in our review below we will list the therapeutic modalities awaiting the evaluation for the only definitive therapy, which is liver transplantation